Design of High Efficiency Cooler for IGBT Module in CRH2 - Gao Feng; Zhang Yi; Pan Xiaoyan (Zhileng xuebao)
For the high-power insulated gate bipolar translator (IGBT) module, which is presently used in the converter of CRH2, four types of high-efficiency cooler for the traction converter of CRH2 were designed. Using FLUENT to simulate four types of cooler models and comprehensively analyzing and comparing the simulation results, cha-30×10 was determined to be the best cooler model, and the optimal model was quadratically optimized. The optimal scheme was determined to be the 160° cooler, and the relationship between the maximum temperature, maximum thermal resistance, pressure drop, and the flowrate of coolant was obtained. With an inlet mass flow rate 0.1 kg/s, the simulation results show that the maximum temperature of the cha-30×10 (160°) cooler is 3 K lower than that of shun- 20×10, and the maximum thermal resistance is 7.8% lower than that of shun-20×10.